2014
DOI: 10.1161/hypertensionaha.113.02330
|View full text |Cite
|
Sign up to set email alerts
|

Enalapril Attenuates the Exaggerated Sympathetic Response to Physical Stress in Prenatally Programmed Hypertensive Rats

Abstract: Adulthood hypertension can be prenatally programmed by maternal dietary protein deprivation. We have shown that the sympathetically-mediated pressor response to physical stress is exaggerated in prenatally programmed hypertensive rats (PPH). The mechanisms underlying this abnormal responsiveness remain undetermined. The renin-angiotensin system is known to effect sympathetic nerve activity. Therefore, the purpose of this study was to determine whether inhibition of the renin-angiotensin system attenuates the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 40 publications
5
33
0
Order By: Relevance
“…This characteristic EPR overactivity has been shown to manifest not only in SHR but also in other models of the disease such as prenatally programmed hypertension (41,44) and angiotensin II-induced hypertension (24). In SHR, 3 mo of voluntary wheel running attenuated the cardiovascular and sympathetic responses to EPR activation.…”
Section: Exercise Training Attenuates Epr Function In Shrmentioning
confidence: 99%
“…This characteristic EPR overactivity has been shown to manifest not only in SHR but also in other models of the disease such as prenatally programmed hypertension (41,44) and angiotensin II-induced hypertension (24). In SHR, 3 mo of voluntary wheel running attenuated the cardiovascular and sympathetic responses to EPR activation.…”
Section: Exercise Training Attenuates Epr Function In Shrmentioning
confidence: 99%
“…Additionally, the sympathetically mediated blood pressure response to exercise is also abnormally elevated in hypertensive animals (32,(41)(42)(43)(44)52) and patients (11,12,36,58). The impairments in functional sympatholysis might be a mechanism by which the blood pressure response to physical exercise is exaggerated in this disease.…”
mentioning
confidence: 99%
“…Finally, it has been proposed that RAS may also be involved in the enhanced renal sympathetic activity ( Figure 5). This latter possibility is supported by studies showing that hypertension is associated to an enhanced AT 1 receptor expression in several areas of the brain and that the intracerebroventricular administration of an ARA induces a significant reduction in BP [120]. It has also been reported that the administration of a CEI prevents the exaggerated renal sympathetic and pressor responses to physical stress in rats with developmental programming of hypertension [121].…”
Section: Sympathetic Nervous Systemmentioning
confidence: 83%